A rare case of hepatic flexure Gastroenteropancreatic neuroendocrine carcinoma (GEP-NEC) - Jasmani, Asraf Haslam; Khazalle, Muhammad Haekal; Oaris, Iqtidaar; Mohamad, Ikhwan Sani (UPM Press, 2022)
A Colorectal neuroendocrine carcinoma (CRNEC) is a rare malignancy of the colon. It is a tumour with a heterogeneous presentation, further complicated by its disunified nomenclature, which imposed a challenge in detection and management. We present a rare case of hepatic flexure neuroendocrine carcinoma in a 47-year-old lady who complained of 5 months history of progressively worsening, intermittent colicky central abdominal pain, altered bowel habit, vomiting, and significant weight loss. She presented with lethargy, distended abdomen and fullness at its centre. The abdominal x-ray showed generalised bowel dilatation, with the subsequent CT scan abdomen showing obstructed hepatic flexure tumour. She underwent emergency exploratory laparotomy and right hemicolectomy with a double-barrel stoma. Intraoperatively, a hepatic flexure tumour, an engorged and nodular appendix with multiple mesenteric lymph nodes. Her recovery was unremarkable. Histopathology examination showed neuroendocrine tumour Grade 3 arising from hepatic flexure with no appendiceal involvement.